Process Development for the Production and Purification of PEGylated RhG-CSF Expressed in Escherichia coli - Mohammadi, Zeinab; Alijanianzadeh, Mahdi; Khalilzadeh, Rassoul; Khodadadi, Sirus (Protein and Peptide Letters, 2022)
Background and Objectives: Recombinant human granulocyte-colony stimulating factor (rhG-CSF) and its PEGylated form (PEG-GCSF) are used in cancer therapy. Thus, developing a more cost-effectively method for expressing rhG-CSF and the PEGylation optimization of rhG-CSF by reaction engineering and subsequent purification strategy is necessary. Methods: RhG-CSF expression in Escherichia coli BL21 (DE3) was carried out by auto-induction batch fermentation and improved for maximizing rhG-CSF productivity. After that, purified rhGCSF was PEGylated using methoxy polyethylene glycol propionaldehydes (mPEG20-ALD). The various conditions effect of extraction and purification of rhG-CSF and PEG-GCSF were assayed. Results: The assessment results revealed that the auto-induction batch cultivation strategy had maximum productivity, and rhG-CSF purity was more than 99%. The obtained data of rhG-CSF PEGylation displayed that the optimized conditions of rhG-CSF PEGylation and purification enhanced homogeneity PEG-GCSF and managed reaction toward optimal yield of PEG-GCSF (70%) and purity of 99.9%. Findings from FTIR, CD, fluorescence spectroscopy, and bioassay revealed that PEGylation was executed exactly in the rhG-CSF N-terminus, and products maintained their conformation properties. Conclusion: Overall, the developed approach expanded strategies for high yield rhG-CSF by simplified auto-induction batch fermentation system and rhG-CSF PEGylation, which are simple and timesaving, economical, and high efficiency.
Keywords: batch fermentation